Nutritional Status and Food Preference Differences Among Primary School Students in Karangasem, Bali - Mellysa Kowara; I Putu Suiraoka; Yessi Crosita Octaria; Eny Kurnia Sari; Agnes A Malipu (Warmadewa University, 2025)
Nutritional status during primary school age is essential for optimal physical growth and cognitive development. Dietary transitions driven by modernization—including increased consumption of fast foods and sweetened beverages—may reduce the intake of nutrient-dense foods. This study aimed to describe the nutritional status and food preferences of students at SDN 2 Besakih, Karangasem, Bali. A cross-sectional study was conducted. Anthropometric measurements were obtained from all students present (n = 211) and assessed using BMI-for-age and height-for-age indicators based on WHO AnthroPlus standards. Food preference data were collected from 72 students selected through stratified sampling using a pictorial Likert-scale questionnaire. Data were analysed using univariate, bivariate, and multifactorial tests. Most students exhibited normal nutritional status, although both undernutrition and overnutrition were present. The leftward shift in BMI-for-age and height-for-age z-score curves indicated vulnerability to undernutrition and stunting. Female students demonstrated significantly higher preference scores for chicken dishes (p = 0.003) and milk-based or sweetened beverages (p = 0.009). Grade level influenced preferences for chicken dishes and beverages, with no significant interaction between gender and grade. Vegetable preference was relatively low across all groups. Primary school children in rural Karangasem face a double burden of malnutrition accompanied by shifting dietary preferences toward less balanced food choices. Strengthening school-based nutrition interventions, including nutrition education, healthy canteen programs, and routine growth monitoring, is critical to fostering healthy dietary habits early in life.